DIAGNOSIS OF ANTIPHOSPHOLIPID SYNDROME IN PEOPLE WITH CLINICAL CRITERIA OF THE DISEASE. EXPERIENCE OF A SEPARATE OUTPATIENT CENTER - T. V. Vavilova; L. A. Isaeva; K. Yu. Grinchenko; Ju. D. Bogatenkova; V. A. Sorokoumov (Атеротромбоз)
Antiphospholipid syndrome (APS) is an immune-mediated violation of coagulation, the diagnosis of which requires mandatory laboratory confirmation. Since the clinical manifestations of APS are extremely diverse, various specialists are involved in the diagnostic process – neurology, cardiologists, surgeons, hematologists, endocrinologists, laboratory medicine specialists, etc. So far, it remains an open question what specialist exactly should make the final diagnosis and supervise patient with APS. The experience of a separate diagnostic center shows the distribution of prescriptions and their compliance with the international recommendations. This study also provides data on the frequency of prescribing laboratory tests to confirm APS, which is 1.2% of all coagulation tests. Among the patients with suspected APS on the basis of clinical signs, only 12.2% of the diagnosis was confirmed. Presents the dangers of obtaining false-positive results that should be taken into account when prescribing laboratory tests.